Arbuscular Mycorrhizal Fungi Confer Salt Tolerance in Giant Reed (Arundo donax L.) Plants Grown Under Low Phosphorus by Reducing Leaf Na+ Concentration and Improving Phosphorus Use Efficiency - Romero-Munar, Antònia; Baraza, Elena; Gulías, Javier; Cabot, Catalina (Frontiers in Plant Science, 2019)
Salinization is one of the major causes of agricultural soil degradation worldwide. In arid and semi-arid regions with calcareous soils, phosphorus (P) deficiency further worsens the quality of salinized soils. Nonetheless, nutrient poor soils could be suitable of producing second-generation energy crops. Due to its high biomass production, Arundo donax L. (giant reed) is one of the most promising species for energy and second-generation biofuel production. A. donax can be propagated by micropropagation, an in vitro technique that produces high number of homogeneous plantlets. However, crop establishment is often compromised due to poor plantlet acclimatization to the soil environment. Arbuscular mycorrhizal fungi (AM) are components of soil-plant systems able to increase root phosphorus uptake and to confer the plant an increase tolerance to salinity with a consequent enhancement effect of plant growth and yield. In the present study, the relative importance of the early symbiosis establishment between AM fungi and A. donax micropropagated plantlets in the response to salt stress under low phosphorus availability was determined. A commercial inoculum which contained two different AM fungi species: Rhizophagus intraradices and Funneliformis mosseae was used. AM-symbionts (AM) and non-symbionts plants were grown at two phosphorus [2.5 μM (C) and 0.5 mM (P)] and three NaCl (1, 75 and 150 mM) concentrations in a room chamber under controlled conditions. After 5 weeks, AM root colonization was 60, 26 and 15% in 1, 75 and 150 mM NaCl-treated plants, respectively. At 1 and 75 mM NaCl, AM plants showed increased growth. In all saline treatments, AM plants had decreased Na+ uptake, Na+ root-to-shoot translocation, Na+/K+ ratio and increased P and K use efficiencies with respect to C and P plants. AM improved the nutritional status of A. donax plants by enhancing nutrient use efficiency rather than nutrient uptake. Increased phosphorus use efficiency in AM plants could have benefited ion (Na+ and K+) uptake and/or allocation and ultimately ameliorate the plant’s response to saline conditions.